Quality of life in patients with juvenile arthritis (according to the data of the SF-36 questionnaire) - Tat'yana Andreevna Shelepina; E S Fedorov; Tatyana Andreevna Shelepina; E S Fedorov (Современная ревматология, 2011)
Objective: to estimate quality of life in adolescents with juvenile arthritis (JA) on the basis of an analysis of the results of SF-36 questionnaire interviews. Subjects and methods. Two groups of patients including 85 adolescents with JA (Group 1) and 34 apparently healthy individuals of their age (Group 2; controls) were examined. There were 63% of females among the patients. Systemic, polyarticular, oligoarticular, and juvenile ankylosing spondylosis JA (JAS) were diagnosed in 16 (19%), 34 (40%), 24 (28%), and 11 (13%) patients, respectively. The examinees' mean age was 15.2±1.1 years (range 14-17 years); the mean disease duration was 6.1±4.6 years (range 1-15 years). The control group comprised 73% of females; the mean age was 15.2+1.1 years (range 14-17 years); the adolescents went to school, they had neither musculoskeletal diseases nor release from physical training classes. The SF-36 questionnaire validated for those older than 14 years was used. Results. In Group 1, physical functions, physical activity, body pain, general health condition, and social functions were significantly worse than those in the controls. At the same time, viability, mental health, and emotional activity proved to be (statistically insignificantly) better in Group 1 than in the controls. In Group 1, the boys had better values of functional functions, physical activity, viability, and mental development while the girls had better values of body pain, general health condition, social functions, and emotional activity. In the control group, all these parameters were lower in the girls than in the boys. In Group 1 boys, all the parameters were significantly worse than those in the healthy peers (controls). Group 1 girls with JA had worse physical functions, physical activity, and pain, but better general health and social functions than the controls. Differences were found in the groups of patients with different types of JA: the parameters were significantly worse in those with systemic and oligoarticular types and better in those with JAS. Conclusion. The application of the SF-36 questionnaire could reveal significantly reduced physical functions in the patients with JA as compared to their healthy peers. It is expedient to use this questionnaire for intergroup comparative studies if sufficient clinical material is available.